The impact of AI-based gamification on student engagement in English writing course - Febriyantina Istiara; Galuh Dwi Ajeng; Aksendro Maximilian; Andri Wicaksono; Ravindra Pratap Singh (Journal of Educational Management and Instruction (JEMIN), 2025)
Active student engagement is a cornerstone of effective pedagogy in writing instruction, yet it remains a significant challenge for educators. This study systematically evaluates the impact of an AI-driven gamification model designed to enhance student participation and motivation. Using a quasi-experimental, mixed-methods design, 50 students were assigned to either an experimental group (n=25) engaging with AI tools (ProWritingAid, Quizizz) or a control group (n=25). The intervention's effects were assessed using validated learning engagement scales and in-depth qualitative interviews. The findings indicate a statistically significant increase in learning engagement for the experimental group, a result attributed to the immediate, personalized feedback and structured, low-stakes practice facilitated by the AI tools. This quantitative outcome was corroborated by qualitative data; thematic analysis revealed overwhelmingly positive student perceptions, with participants citing heightened motivation, reduced writing apprehension, and a greater sense of agency. Students specifically valued the non-judgmental feedback from AI and the competitive yet collaborative nature of the gamified tasks. The implications of this study are twofold. Practically, it offers a replicable pedagogical model for educators seeking to transform passive writing classrooms into active, technology-enhanced learning spaces. Theoretically, it contributes to the literature at the intersection of applied AI and composition pedagogy by demonstrating how gamification principles can be powerfully augmented by AI to address long-standing engagement challenges. This research thus provides a compelling blueprint for designing more effective, student-centered writing curricula in the digital age.